Role of fine-needle aspiration cytology in the diagnosis of major salivary gland tumors: A study with histological and clinical correlation - Shetty, Archana (J Oral Maxillofac Pathol, 2016)
INTRODUCTION: Neoplastic lesions of salivary glands present an interesting subject because of their histologic diversification. Complex features exhibited by them have aroused considerable speculations concerning their histogenesis and continues to hold the interest of clinicians and pathologists. Major salivary glands are superficial and have easy accessibility for fine-needle aspiration cytology (FNAC). These glands are generally not subjected to incisional or core needle biopsy, because of the possible risks of fistula formation and tumor seedling. FNAC diagnosis of major salivary gland neoplasms aids in proper planning of required surgery and avoidance of the same in cases of non-neoplastic lesions. MATERIALS AND METHODS: Cytological features of major salivary gland tumors diagnosed on FNAC were studied over a period of one and a half years. Cytological and architectural patterns in smears were compared with histopathological features in cases where the specimens were available with a note on the age, sex and presenting complaints. Statistical Analysis: Analysis of variance (ANOVA) was used to find the significance of study parameters. Chi-square/Fisher Exact was used to find the significance of study parameters on categorical scale between two or more groups. P value of <0.05 was considered to be significant. RESULTS: A total of 114 salivary gland FNACs were done, 75 patients were clinically suspected to be neoplasms. The peak incidence was in the third to fourth decade of life with a female preponderance. Parotid was the most commonly affected gland (80%) with pleomorphic adenoma and mucoepidermoid carcinoma (10.7%) being the most common benign and malignant tumors respectively. The diagnostic accuracy of FNAC was 97.6%. Warthins tumor was misdiagnosed and was associated with a strong smoking history. CONCLUSION: Salivary gland neoplasms constitute a small but significant percentage of head and neck tumors. FNAC is inexpensive, quick, and aids in the preoperative diagnosis and planning of surgery.